2021
DOI: 10.1186/s12984-021-00969-2
|View full text |Cite
|
Sign up to set email alerts
|

Eye-gaze control of a wheelchair mounted 6DOF assistive robot for activities of daily living

Abstract: Background Building control architecture that balances the assistive manipulation systems with the benefits of direct human control is a crucial challenge of human–robot collaboration. It promises to help people with disabilities more efficiently control wheelchair and wheelchair-mounted robot arms to accomplish activities of daily living. Methods In this study, our research objective is to design an eye-tracking assistive robot control system capa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…At the same time, most of the tablet-based UIs offer the possibility to connect additional input devices such as head or eye control. Sunny et al [ 31 ] also followed such an approach. The authors investigated the usability of a control system consisting of an eye-gaze interface and a tablet-based graphical UI for a wheelchair-mounted xArm 6 from UFactory in different manipulation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, most of the tablet-based UIs offer the possibility to connect additional input devices such as head or eye control. Sunny et al [ 31 ] also followed such an approach. The authors investigated the usability of a control system consisting of an eye-gaze interface and a tablet-based graphical UI for a wheelchair-mounted xArm 6 from UFactory in different manipulation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the values of are expressed in Eqs. (2). Thus, considering two rotation about the ̂ and ̂ axis of the moving platform by an angle and , respectively, the following relation for the points holds:…”
Section: Inverse Kinematicsmentioning
confidence: 99%
“…Upper limb amputation is the removal of any part of the forearm or arm. Only in the United States, this condition affects approximately 41,000 citizens [1,2]. Besides, according to the results of Ziegler-Graham K. et al, this value may double by 2050 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Their research demonstrated how alternate means of interaction can be achieved by detecting and tracking very small organs of the human body like eyes and how a GUI can help to improve the interaction. Similarly, Sunny et al [ 31 ] developed a wheelchair mounted robotic arm that can be controlled using eye gaze. In this system also, a GUI was used and it was placed on the wheelchair along with the robotic arm.…”
Section: Introductionmentioning
confidence: 99%